DEVELOPMENT AND CALCULATION METHOD OF FINITE ELEMENT UNIT CONNECTIONS STEEL CONCRETE COLUMNS WITH MONOLITHIC SLABS - and and (Municipal economy of cities (Technical science), 2013)
We give a new construction site, developed to resolve problems desaturation reinforcement and examined its stress-strain state.